Comparative transcriptome analysis reveals molecular strategies of oriental river prawn Macrobrachium nipponense in response to acute and chronic nitrite stress. (January 2016) - Xu, Zhixin; Li, Tongyu; Li, Erchao; Chen, Ke; Ding, Zhili; Qin, Jian G.; Chen, Liqiao; Ye, Jinyun
Abstract: Macrobrachium nipponense is an economically and nutritionally important species threatened by ambient superfluous nitrite. De novo RNA-Seq was used to explore the molecular mechanism in M. nipponense exposed to the acute nitrite stress (26.05 mg/L nitrite-N) for 24 h and the chronic nitrite stress (1.38 mg/L nitrite-N) for 28 d A total of 175.13 million reads were obtained and assembled into 58, 871 unigenes with an average length of 1028.7 bp and N50 of 1294 bp. Under the acute and chronic nitrite stress trials, 2824 and 2610 unigenes were significantly expressed. In GO analysis and KEGG pathway analysis, 30 pathways were significantly different between the two treatments while four pathways were in common and the markedly altered pathways were divided into four sections as immunity, metabolism, cell and others. The immunity section revealing the different depth of immunity provoked by nitrite stress contained the most pathways including the important pathways as phagosome, folate biosynthesis, glycerolipid metabolism, glycine, serine and threonine metabolism, amino sugar and nucleotide sugar metabolism under the acute nitrite stress, and lysosome, alanine, aspartate and glutamate metabolism, arginine and proline metabolism under the chronic nitrite stress. This is the first report of responses of M. nipponense under acute and chronic nitrite stress through de novo transcriptome sequencing on the transcriptome level. The results of transcriptome analysis improve our understanding on the underlying molecular mechanisms coping with nitrite stress in crustacean species. Highlights: Transcriptome analysis of the hepatopancreas in Macrobrachium nipponense Molecular strategies of M. nipponense responding to acute nitrite stress. Molecular strategies of M. nipponense responding to chronic nitrite stress.